The Effect of Various β Values on Image Quality and Semiquantitative Measurements in 68Ga-RM2 and 68Ga-PSMA-11 PET/MRI Images Reconstructed With a Block Sequential Regularized Expectation Maximization Algorithm - Baratto, Lucia; Duan, Heying; Ferri, Valentina; Khalighi, Mehdi; Iagaru, Andrei (Clinical nuclear medicine, 2020)
To compare the block sequential regularized expectation maximization (BSREM) algorithm with the ordered subsets expectation maximization (OSEM) algorithm and to evaluate how different penalty factors (b values) influence image quality and SUV measurements. We analyzed data from 78 prostate cancer patients who underwent Ga-RM2 (n = 42) or Ga-prostate-specific membrane antigen (PSMA)-11 (n = 36) PET/MRI. The raw PET data were retrospectively reconstructed using both time-of-flight (TOF)-BSREM with b values of 250, 350, 500, 750, and 1000 and TOF-OSEM. Each reconstruction was reviewed independently by 3 nuclear medicine physicians and scored qualitatively using a Likert scale (1 = poor, 5 = excellent quality). SUV measurements were analyzed as well. Fifty-seven lesions were detected (21 on Ga-RM2 and 36 on Ga-PSMA-11 PET/MRI); SUVmax decreased with the increase of β values for both tracers. Background noise (SUVsd) decreased with increasing of β values for both tracers. The mean ± SD scores for Ga-RM2 PET images were 2.4 ± 0.5 for b = 250 reconstructions, 3.2 ± 0.6 for b = 350, 4 ± 0.6 for b = 500, 4.5 ± 0.5 for b = 750, 4.4 ± 0.7 for b = 1000, and 3.4 ± 0.6 for TOF-OSEM. The mean ± SD scores for Ga-PSMA-11 PET images were 3.2 ± 0.8 for b = 250 reconstructions, 4.1 ± 0.8 for b = 350, 4.7 ± 0.6 for b = 500, 4.8 ± 0.4 for b = 750, 4.7 ± 0.6 for b = 1000, and 3.8 ± 0.5 for TOF-OSEM. Time-of-flight-BSREM algorithm improves image quality. Different b values should be used for different Ga-labeled radiopharmaceuticals such as those targeting GRPR and PSMA receptors. Once selected, the same b value should be consistently used because SUVmax measurements differ with different b values.